Depression - the first symptom of a brain tumor or a consequence of the process neoplastic process - a review of the literature - Klaudia Antkowiak; Hubert Ciecierski-Koźlarek; Urszula Żurek; Ignacy Tołwiński; Zofia Kędzierska; Klaudia Dadas; Aleksandra Świercz; Dominika Małachowska; Kateryna Shved (Kazimierz Wielki University, 2023)
Introduction and objective CNS malignancies account for about 1.6% of all diseases today. In people diagnosed with a brain tumor with a poor prognosis, we often see disorders from the psychiatric spectrum, most often depressive disorders. In this paper, we want to focus on whether depression occurs as a sequel to cancer or perhaps is the first of the symptoms of a CNS tumor. Review methods For the analysis, the PubMed medical database was searched, and articles containing studies and case reports of people with CNS tumor and depressive disorders that occurred either before diagnosis or at any time during the course of the disease were selected Abbreviated description of the state of knowledge CNS tumors produce symptoms such as epilepsy, visual disturbances, paresis, but also behavioral disorders. This is determined by the location of the tumor. Depression is a mental disorder manifested mainly by lowered mood. This disorder can coexist with tumors occurring in the frontal lobe or be present regardless of the location of the tumor, in people diagnosed with a tumor with a poor prognosis. Summary Analyzing the selected articles, we see that in people who were diagnosed with a tumor located in the frontal lobe, often the first symptom was depressive disorders, which even preceded neurological symptoms. When depression is diagnosed, appearing suddenly and refractory to treatment, one should consider whether there is an underlying pathological lesion in the CNS. Unfortunately, there are no specific guidelines for imaging studies in depressive disorders. People who suffer from malignant tumors with a poor prognosis should be cared for by a psychologist, because as the disease progresses, the symptoms worsen, affecting the prognosis.